The Implementation of Investigative Journalism in Tempo Magazine "Treasure of Tax Officials" - Suprianto, Bagja; Adnan, Iis Zilfah; Purnama, Feri (International Journal of Science and Society, 2023)
Investigative journalism is a form of news coverage in which journalists delve deeply into information or events that may expose corruption, analyze government policies or private company practices, or uncover economic, political, and cultural trends. Investigative news coverage is typically obtained by investigative journalists when they are interested in an issue and have a strong desire to find out something. Therefore, the work of investigative journalism is not constrained by time pressure; often, investigative journalists spend years, even decades, working on a single investigative report. In this study, the author employs the theory of critical discourse analysis by Teun A Van Dijk, which focuses on the textual dimensions of a magazine, news, or broadcast. Based on this, it is important to conduct a critical discourse analysis of Tempo magazine. This research analyzes two issues: microstructure and superstructure. The study also uses a qualitative descriptive approach, with observation as the data collection method. The results of this research show that, in terms of microstructure and superstructure discourse, Tempo magazine with the title "TREASURE OF TAX OFFICIALS" can be considered a means for the implementation of investigative journalism through the careful choice of words, language, sentence structure, and style, successfully uncovering a case of tax officials' corruption.